Activists' Struggle Under the Hegemony of a Zalim Regime: Perspective of Hr. Ibn Hibban No. 286 - Cyndi Hidayat Attazkie; Mohammad Shodiq Ahmad (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2025)
The struggle of activists against oppressive regimes is a historical reality that has been repeated in various eras and places. Authoritarian regimes often suppress activist movements through various forms of repression, both structural and psychological. This study examines the dynamics of activists' struggle under the pressure of oppressive rule, with reference to the hadith narrated by Ibn Hibban No. 286 which asserts that conveying the truth in the face of oppressive rulers is the most important form of jihad. The approach used is qualitative through hadith studies and historical analysis, with reference to classical and contemporary literature, including books of hadith, tafsir, and relevant scientific research. The results of the study show that the form of activist resistance is not always confrontational, but can also be realized through da'wah, education, and diplomacy. This research provides a deeper understanding of how activists' struggles can take place ethically and with dignity, even under the pressure of an oppressive regime.